Green innovation Bamboo House Jemparing Wangi: collaboration Pertamina and residents of Kampung Papring, Banyuwangi - Narotama Aulia Fazri; Surya Suganda; Jimmy Wijaya; Sudarmiatin; Trisetia Wijijayanti (Abadi Institute, 2026)
This study discusses the green entrepreneurship model developed through Pertamina'S CSR program in Kampung Papring, Banyuwangi, emphasizing the role of biogas innovation and the use of bamboo as the foundation of the local economy. The Jemparing Wangi Program is designed through a comprehensive social mapping process, involving FGDs, village potential surveys, and identification of basic community needs. The mapping results were used to build relevant interventions, including the establishment of bamboo houses as training centers, production, environmental education, and collaboration spaces for residents. Rumah Bambu plays an important role in creating a green business ecosystem, especially through the development of bamboo handicraft products such as woven, bags, besek, lanterns, and decorative products that have economic value. Energy innovation through the use of biogas from livestock waste is a key element in the circular economy practices developed at Papring. Biogas is used for household needs and supports the production process, thus helping to reduce the use of conventional fuels and reduce environmental pollution. In addition, this CSR program strengthens women and youth-based MSME groups through entrepreneurship training, product quality improvement, and marketing access through CSR e-catalogs and local retail networks. Multi-stakeholder collaboration including the community, village government, media, and Pertamina encourages the birth of an adaptive, creative, and independent social environment. Overall, research shows that the integration of environmental innovation, strengthening community institutions, and structured CSR support can drive socio-economic transformation of rural communities. This model of green entrepreneurship deserves to be replicated in other areas that have the potential for biomass and local crafts, as a real contribution to sustainable development.